PTH-003 An Audit on two week wait Referrals for Suspected Lower Gi Cancer for Iron Deficiency Anaemia – too Often an Inappropriate Referral. (4th June 2013) - Aziz, S; Wood, E; Marelli, L
Abstract : Introduction: NICE guidelines state that unexplained iron deficiency anaemia (IDA) in men and non-menstruating women requires an urgent two week wait (2ww) referral for suspected cancer. These patients require assessment with upper endoscopy and colonoscopy according to BSG guidelines. IDA is defined as a microcytic anaemia with the presence of any of the following serum markers: low ferritin, low transferrin saturation, low iron or raised TIBC. The aim of this audit was to assess how many lower GI 2ww referral patients for IDA actually had IDA. Methods: We analysed all consecutive 2ww referrals for suspected lower GI cancer for IDA in our Hospital from May until October 2012. Patients' demographics, medical history, medications and blood test results (FBC, haematinics, eGFR, CRP, Hb electrophoresis) were collected using the General Practitioner (GP) referral letter and the hospital computer system. IDA was identified as microcytic anaemia with low ferritin; if ferritin was normal but unreliable (concomitant high CRP), we identified IDA as low transferrin saturation with high TIBC. Results: A total of 36 patients (mean age 71±11; M:F = 19:17) were referred as 2ww with asymptomatic IDA. IDA was confirmed in 20 patients (55%). 6 patients (17%) did not have iron deficiency (see table ): 3 of them had colonoscopy and 2 had CT abdomen (unfit for colonoscopy), none had significant pathology; one was not investigated. 10 patients (28%) had insufficient blood tests to define the cause of the anaemia: ferritin not available (2), normal ferritin with high CRP and no other iron markers available (6), normal ferritin with no inflammatory markers available (2). Conclusion: One in six (6/36) patients referred urgently for IDA and suspected lower GI cancer did not have IDA, and the majority were over 80 with multiple co-morbidities. Approximately 1 patient in 4 (10/36) did not have appropriate blood tests performed to assess their anaemia. We recommend GPs perform a full set of haematinics prior to referring patients with IDA and the results should be included in the 2ww referral form. If haematinics are not available at the time of assessment, these should be checked before booking endoscopic investigations. We are amending our referral form accordingly, implementing teaching sessions for GPs and re-auditing in 1 year time. We anticipate a reduction in inappropriate 2ww referrals and subsequent endoscopic requests. Disclosure of Interest: None Declared.